Integrated Science Learning Devices on Substances and Their Characteristics Material with Character Enrichment Through the Application of Problem-Based Learning - Jenni Sari; Rayandra Asyhar; Sri Purwaningsih (Integrated Science Education Journal, 2023)
Purpose of the study: The purpose of this study is how to find out the process of developing learning devices using the PBL model with character enrichment in the substance material and its characteristics which were developed according to experts. Methodology: The research design used by researchers is a quantitative research type of quasi-experimental design using a pretest-posttest control group design. It is done to investigate causal hypotheses about causation that can be manipulated by comparing one or more experimental groups that are treated with one comparison group that is not treated. Main Findings: Based on the analysis of the data and the discussion above, it can be concluded that the students' ability in science subjects on the substance and its characteristics is in the good category. This shows that the application of problem-based learning models can improve students' thinking skills. This is reinforced by testing the hypothesis through the independent sample t-test that there is a significant difference between before being given treatment and after being given treatment Novelty/Originality of this study: Following the era of the industrial revolution 5.0, character-based learning must be developed. Therefore, this research produces science learning tools with problem-based learning in the material and its characteristics.